2014
DOI: 10.2190/cs.15.4.b
|View full text |Cite
|
Sign up to set email alerts
|

Structured Opportunities: Exploring the Social and Academic Benefits for Peer Mentors in Retention Programs

Abstract: Informed by the experiences of former peer mentors, this qualitative study examines the structure of opportunity of a university retention program. Extending the concept of social capital, the study investigates the experiences of students who served as peer mentors, and how their involvement in the retention program has influenced their social and academic development while in college. Findings suggest that employing peer mentors can be mutually beneficial to retention efforts since the peer mentors were trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…For example, with respect to benefits reported by mentors, we found that a large percentage of mentors enjoyed providing assistance to, and forming personal relationships with mentees, which was consistent with previous research (Good et al, 2000;Heirdsfield et al, 2008;Hill & Reddy, 2007;Holt & Berwise, 2012;Kiyama & Luca, 2013;National Resource Center, 2009;Reyes, 2011), as was our subtheme of improved writing skills (National Resource Center, 2009). Mentors' perceived improvement in their organizational skills also was consistent with prior research (Harmon, 2006;National Resource Center, 2009), as was the subtheme of enhanced self-awareness (Harmon, 2006;Hill & Reddy, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For example, with respect to benefits reported by mentors, we found that a large percentage of mentors enjoyed providing assistance to, and forming personal relationships with mentees, which was consistent with previous research (Good et al, 2000;Heirdsfield et al, 2008;Hill & Reddy, 2007;Holt & Berwise, 2012;Kiyama & Luca, 2013;National Resource Center, 2009;Reyes, 2011), as was our subtheme of improved writing skills (National Resource Center, 2009). Mentors' perceived improvement in their organizational skills also was consistent with prior research (Harmon, 2006;National Resource Center, 2009), as was the subtheme of enhanced self-awareness (Harmon, 2006;Hill & Reddy, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Improved time management and organizational skills also have been consistent themes in mentors' reflections (Hall & Jaugietis, 2011;Harmon, 2006;National Resource Center, 2009), which relates to a larger theme of enhanced self-awareness (Harmon, 2006;Hill & Reddy, 2007). Other reported benefits, such as enhanced awareness of social justice issues (Kiyama & Luca, 2013), leadership skills (Good et al, 2000), or group-guidance skills (Skaniakos, Penttinen, & Lairio, 2014) may be more program specific, but significant nonetheless. The numerous common themes that have emerged from these studies are notable given the heterogeneity in program structure, curriculum, and program participants.…”
Section: Purpose Statementmentioning
confidence: 91%
See 1 more Smart Citation
“…These peer tutors are selected for their high academic performances and social skills and typically receive specialized training under the aegis of the college's educational support services including Learning Assistance Center or Academic Enrichment. Higher education research on peer teaching/learning consistently shows both the peer learner and the peer-teacher experience significant gains in learning from the collaborative interactions (Cottam, Menzel, & Greenblatt, 2011;Kiyama & Luca, 2016). Additionally, the peer-tutoring students display deeper levels of understanding of the concepts of the subjects they teach to other students (Benware & Deci, 1984) and achieve greater mastery of the course content (Philipp, Tretter, & Rich, 2016), and show positive impact on overall student engagement and retention in students with underdeveloped basic-academic skills (Callahan, 2009;Peck, 2011;Flores & Duran, 2013).…”
Section: Peer Tutoringmentioning
confidence: 99%
“…The notion of peer mentoring suggests an ongoing relationship whereby a "more experienced student helps a less experienced student (mentee) improve overall academic performance by providing advice, support, and knowledge" (Moschetti, Plunkett, Efrat, & Yomtov, 2017, p. 2). Peer mentoring has been noted as an influential factor in the retention of college students, particularly among first-generation college students, first-year college students, and racial/ethnic minorities (Asgari & Carter, 2016;Jaswal & Jaswal, 2008;Keup, 2016;Kiyama & Luca, 2014;Rios-Ellis et al, 2015;Shotton et al, 2007). Peer mentoring has been linked to increases in students" academic performance, selfefficacy, and social integration (Asgari & Carter, 2016;Hall & Jaugietis, 2011;Morales et al, 2016;Moschetti, Plunkett, Efrat, & Yomtov, 2017).…”
Section: Peer Mentorshipmentioning
confidence: 99%